Optimal. Leaf size=26 \[ x+e^{\frac {2 e^2 (4-x) x}{3 (-4+x)}} x^2 \]
________________________________________________________________________________________
Rubi [A] time = 0.09, antiderivative size = 16, normalized size of antiderivative = 0.62, number of steps used = 10, number of rules used = 5, integrand size = 29, \(\frac {\text {number of rules}}{\text {integrand size}}\) = 0.172, Rules used = {12, 1593, 2196, 2176, 2194} \begin {gather*} e^{-\frac {2 e^2 x}{3}} x^2+x \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
Rule 12
Rule 1593
Rule 2176
Rule 2194
Rule 2196
Rubi steps
\begin {gather*} \begin {aligned} \text {integral} &=\frac {1}{3} \int \left (3+e^{-\frac {2 e^2 x}{3}} \left (6 x-2 e^2 x^2\right )\right ) \, dx\\ &=x+\frac {1}{3} \int e^{-\frac {2 e^2 x}{3}} \left (6 x-2 e^2 x^2\right ) \, dx\\ &=x+\frac {1}{3} \int e^{-\frac {2 e^2 x}{3}} x \left (6-2 e^2 x\right ) \, dx\\ &=x+\frac {1}{3} \int \left (6 e^{-\frac {2 e^2 x}{3}} x-2 e^{2-\frac {2 e^2 x}{3}} x^2\right ) \, dx\\ &=x-\frac {2}{3} \int e^{2-\frac {2 e^2 x}{3}} x^2 \, dx+2 \int e^{-\frac {2 e^2 x}{3}} x \, dx\\ &=x-3 e^{-2-\frac {2 e^2 x}{3}} x+e^{-\frac {2 e^2 x}{3}} x^2-\frac {2 \int e^{2-\frac {2 e^2 x}{3}} x \, dx}{e^2}+\frac {3 \int e^{-\frac {2 e^2 x}{3}} \, dx}{e^2}\\ &=-\frac {9}{2} e^{-4-\frac {2 e^2 x}{3}}+x+e^{-\frac {2 e^2 x}{3}} x^2-\frac {3 \int e^{2-\frac {2 e^2 x}{3}} \, dx}{e^4}\\ &=x+e^{-\frac {2 e^2 x}{3}} x^2\\ \end {aligned} \end {gather*}
________________________________________________________________________________________
Mathematica [A] time = 0.01, size = 16, normalized size = 0.62 \begin {gather*} x+e^{-\frac {2 e^2 x}{3}} x^2 \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
________________________________________________________________________________________
fricas [A] time = 0.55, size = 12, normalized size = 0.46 \begin {gather*} x^{2} e^{\left (-\frac {2}{3} \, x e^{2}\right )} + x \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
giac [B] time = 0.24, size = 43, normalized size = 1.65 \begin {gather*} \frac {1}{2} \, {\left (2 \, x^{2} e^{4} + 6 \, x e^{2} + 9\right )} e^{\left (-\frac {2}{3} \, x e^{2} - 4\right )} - \frac {3}{2} \, {\left (2 \, x e^{2} + 3\right )} e^{\left (-\frac {2}{3} \, x e^{2} - 4\right )} + x \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maple [A] time = 0.04, size = 13, normalized size = 0.50
method | result | size |
risch | \(x +x^{2} {\mathrm e}^{-\frac {2 \,{\mathrm e}^{2} x}{3}}\) | \(13\) |
norman | \(x +x^{2} {\mathrm e}^{-\frac {2 \,{\mathrm e}^{2} x}{3}}\) | \(15\) |
default | \(x -18 \,{\mathrm e}^{-2} \left (-{\mathrm e}^{-2} \left (-\frac {{\mathrm e}^{-\frac {2 \,{\mathrm e}^{2} x}{3}} {\mathrm e}^{2} x}{6}-\frac {{\mathrm e}^{-\frac {2 \,{\mathrm e}^{2} x}{3}}}{4}\right )-{\mathrm e}^{-2} \left (\frac {{\mathrm e}^{-\frac {2 \,{\mathrm e}^{2} x}{3}} {\mathrm e}^{4} x^{2}}{18}+\frac {{\mathrm e}^{-\frac {2 \,{\mathrm e}^{2} x}{3}} {\mathrm e}^{2} x}{6}+\frac {{\mathrm e}^{-\frac {2 \,{\mathrm e}^{2} x}{3}}}{4}\right )\right )\) | \(87\) |
derivativedivides | \(-{\mathrm e}^{-2} \left (-{\mathrm e}^{2} x -18 \,{\mathrm e}^{-2} \left (-\frac {{\mathrm e}^{-\frac {2 \,{\mathrm e}^{2} x}{3}} {\mathrm e}^{2} x}{6}-\frac {{\mathrm e}^{-\frac {2 \,{\mathrm e}^{2} x}{3}}}{4}\right )-18 \,{\mathrm e}^{-2} \left (\frac {{\mathrm e}^{-\frac {2 \,{\mathrm e}^{2} x}{3}} {\mathrm e}^{4} x^{2}}{18}+\frac {{\mathrm e}^{-\frac {2 \,{\mathrm e}^{2} x}{3}} {\mathrm e}^{2} x}{6}+\frac {{\mathrm e}^{-\frac {2 \,{\mathrm e}^{2} x}{3}}}{4}\right )\right )\) | \(90\) |
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maxima [B] time = 0.36, size = 43, normalized size = 1.65 \begin {gather*} \frac {1}{2} \, {\left (2 \, x^{2} e^{4} + 6 \, x e^{2} + 9\right )} e^{\left (-\frac {2}{3} \, x e^{2} - 4\right )} - \frac {3}{2} \, {\left (2 \, x e^{2} + 3\right )} e^{\left (-\frac {2}{3} \, x e^{2} - 4\right )} + x \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
mupad [B] time = 0.06, size = 12, normalized size = 0.46 \begin {gather*} x+x^2\,{\mathrm {e}}^{-\frac {2\,x\,{\mathrm {e}}^2}{3}} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
sympy [A] time = 0.11, size = 14, normalized size = 0.54 \begin {gather*} x^{2} e^{- \frac {2 x e^{2}}{3}} + x \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________